Reducing of Torque and Flux Ripples DTC of IM Based on Predictive Control, ISSN 1582-4594 - Djeghdali Lakhdar; Naceri Farid; Sebti Belkacem (Journal of Electrical Engineering, Roumanie, 2015)
We present in this paper a comparative study between two control strategies of electrical machines: Direct Torque Control (DTC-SVM), and Predictive Direct Torque Control (MPDTC). The first algorithm based on PI controllers, where the torque and the flux are regulated by a PI controller; we present a conception method of the PI controllers, associated with the flux and the torque regulation loops and gives analytical formulas for the proportional and integral gains. We also present in the second algorithm. The Predictive Direct Torque Control based on the linearization input-output of the machine. The technique of the linearization is used to give a model linearized and uncoupled from the machine for the anticipation of future behavior of the output. Following the formulation of both approaches, their implementation in the Matlab-Simulink environment has been treated. It has been found that the second approach MPDTC yields high dynamic performances in the whole speed range. These performances are characterized by a low torque ripple. However, requires much more CPU time than the first one.